2022
DOI: 10.1029/2021rg000765
|View full text |Cite
|
Sign up to set email alerts
|

Per‐ and Polyfluoroalkyl Substances (PFAS) in Subsurface Environments: Occurrence, Fate, Transport, and Research Prospect

Abstract: Per‐ and polyfluoroalkyl substances (PFASs), also known as “forever chemicals,” are manmade chemicals that have been increasingly detected in various geological settings since the early 2000s. The soil and subsurface environments are the geological media commonly affected by PFAS. We conducted a comprehensive review of peer‐reviewed articles published from 2010 through 2022 concerning the fate and transport of PFAS in subsurface environments. This review is organized into different subsections, covering the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 200 publications
(496 reference statements)
1
50
0
Order By: Relevance
“…The coordinates of the geometrically optimized AmPr-FHxSA-PrA and AmPr-FHxSA are provided in the SI (Tables S16 and S17). The computational predictions may explain why some zwitterionic PFAS may behave as "neutral" molecules with zero net charge 20 and why zwitterion mass retained was related to the largely aliphatic OC in this soil, whereas no such relationship was found for anionic C ≤ 7 PFAS.…”
Section: Model Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…The coordinates of the geometrically optimized AmPr-FHxSA-PrA and AmPr-FHxSA are provided in the SI (Tables S16 and S17). The computational predictions may explain why some zwitterionic PFAS may behave as "neutral" molecules with zero net charge 20 and why zwitterion mass retained was related to the largely aliphatic OC in this soil, whereas no such relationship was found for anionic C ≤ 7 PFAS.…”
Section: Model Validationmentioning
confidence: 99%
“…35 In summary, most researchers conclude that no single soil or PFAS molecular property can fully capture PFAS retention in soil. 22,26,35,38,40,55,56 We took this situation as a call to reconcile and improve knowledge regarding the mechanistic connection between those chemical and physical sorbent (soil) and sorbate (PFAS) properties 20,57 that are relevant for retention and transport. 11,15,58 Accordingly, our overarching goal was to develop a generalizable model of PFAS retention in saturated soils of AFFF-impacted source zones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nevada, PFSAs were detected at higher concentrations ranging from 129.8 to 257 ng/g dw compared to PFCAs at 88.6 to 143.1 ng/g dw (Bai and Son 2021). The higher concentrations of PFSAs in sediments compared to PFCAs could be attributed to the former's higher hydrophobicity (Lyu et al 2022). Investigations into seasonal variations found that total PFAS levels during summer (53.5 ng/g dw) were much lower than winter concentrations (292.1 ng/g dw).…”
Section: Pfass Measured In Surface Waters Stormwater and Sedimentmentioning
confidence: 99%